A mixed-methods longitudinal evaluation of a one-day mental health wellness intervention. (March 2017) - Doyle, Louise; de Vries, Jan; Higgins, Agnes; Keogh, Brian; McBennett, Padraig; O'Shea, Marié T
Objectives: This study evaluated the impact of a one-day mental health Wellness Workshop on participants' mental health and attitudes towards mental health. Design: Convergent, longitudinal mixed-methods approach. Setting: The study evaluated Wellness Workshops which took place throughout the Republic of Ireland. Method: Questionnaires measuring hope, mental health self-efficacy, attitudes towards mental health and perceived impact on wellbeing were administered to participants before the workshop ( n  = 415), 1 week after ( n  = 221) and 3 months after ( n  = 110). Semi-structured interviews were carried out with 24 participants to generate a more in-depth understanding of the impact of the workshop. Results: Quantitative findings relating to hope, mental health self-efficacy and attitudes towards mental health did not identify statistically significant changes; however, participants' perceptions of the effect of the workshop on wellbeing suggested a positive impact which was maintained over time. Qualitative findings, however, suggested that hope and self-efficacy were improved and the simplicity and utility of the wellness strategies disseminated in the workshop, in addition to the warmth and openness of the narrative approach used by the facilitators, were central to the perceived positive impact. Conclusion: This evaluation demonstrates the potential for wellness interventions to have a subjective improvement in wellbeing in members of the general public.